2022
DOI: 10.1021/acs.langmuir.2c01730
|View full text |Cite
|
Sign up to set email alerts
|

A Combinatorial Study Investigating the Growth of Ultrasmall Embedded Silver Nanoparticles upon Thermal Annealing

Abstract: Ultrasmall nanoparticles (NPs) with a high active surface area are essential for optoelectronic and photovoltaic applications. However, the structural stability and sustainability of these ultrasmall NPs at higher temperatures remain a critical problem. Here, we have synthesized the nanocomposites (NCs) of Ag NPs inside the silica matrix using the atom beam co-sputtering technique. The post-deposition growth of the embedded Ag NPs is systematically investigated at a wide range of annealing temperatures (ATs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…35 Recently, our group highlighted the significance of embedded nanocomposites (NCs) for the structural stability of Ag/SiO 2 . 36 We showed that Ag NPs remain in the ultra-small size region up to 800 °C, beyond which the size of the NPs increases rapidly due to the Ostwald ripening process. Therefore, the NCs of the embedded NPs are found to be best suited to ensure the stability of ultra-small NPs, owing to their higher active surface area as compared to the NPs of size greater than 10 nm, which is required in industry for improved activity and application efficiency.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…35 Recently, our group highlighted the significance of embedded nanocomposites (NCs) for the structural stability of Ag/SiO 2 . 36 We showed that Ag NPs remain in the ultra-small size region up to 800 °C, beyond which the size of the NPs increases rapidly due to the Ostwald ripening process. Therefore, the NCs of the embedded NPs are found to be best suited to ensure the stability of ultra-small NPs, owing to their higher active surface area as compared to the NPs of size greater than 10 nm, which is required in industry for improved activity and application efficiency.…”
Section: Introductionmentioning
confidence: 79%
“…44 Similar to AuAg/SiO 2 NCs, Ag/SiO 2 NCs also showed an overall red-shift in the LSPR peak position with an increase in the AT, attributed to an increase in the size of the embedded NPs as previously reported. 36…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations